Effects of Positioning on Complications of Preterm Infants with Respiratory Distress Syndrome Treated with Nasal Continuous Positive Airway Pressure: A Randomized Clinical Trial - Sheida Amini; Behzad Barekatain; Majid Mohammadizadeh; Silva Hovsepian (Mashhad University of Medical Sciences, 2023)
Background: Nasal Continuous Positive Airway Pressure (N-CPAP) is the standard method of respiratory support in neonatal intensive care units, and this method is used for almost all infants with respiratory distress syndrome (RDS) for respiratory support. The position of infants under N-CPAP (prone and supine) affects the amount of blood supply. This study aimed to compare the prone \\and supine positions, followed by the investigation of their effects on various respiratory parameters and prematurity complications in premature infants with RDS treated with N-CPAP.Methods: This randomized clinical trial was conducted on 127 premature infants under N-CPAP treatment in the neonatal intensive care units of Al-Zahra and Shahid Beheshti hospitals, Isfahan, Iran. Babies were placed in two groups of 68 and 59 cases with supine and prone positions, respectively. The duration of N-CPAP, the number of prescribed doses of surfactant, the need for mechanical ventilation, time to full feed, and positive end-expiratory pressure (PEEP) were investigated in this study. The obtained data were then analyzed using SPSS software (version 22).Results: The mean±SD values of gestational age and birth weight of the neonates were 31.88±1.30 weeks and 1672.40±443.67 g, respectively. The frequency of using different modes of mechanical ventilation was significantly lower in the prone position group, compared to the supine position group ([17% vs. 32.4%], X2[3, N=127]=7.95, P<0.05). There was a significant correlation between position and using mechanical ventilation during the first 72 hours (P=0.04, Correlation Coefficient=0.182). Multivariate analysis indicated a significant correlation between position and mean time of PEEP (P<0.001, F=13.67), mean of surfactant use (P=0.013, F=6.38), and time to full feed (P=0.002, F=10.29).Conclusion: The results of this study showed that placing preterm infants with RDS who are treated with N-CPAP in the prone position reduces complications related to being preterm or using N-CPAP.